Correlated Prompt Fission Data in Transport Simulations - Talou, P; Vogt, R; Randrup, J; Rising, M E; Pozzi, S A; Verbeke, J; Andrews, M T; Clarke, S D; Jaffke, P; Jandel, M; Kawano, T; Marcath, M J; et al. (arXiv.org, 2018)
Detailed information on the fission process can be inferred from the observation, modeling and theoretical understanding of prompt fission neutron and \(γ\)-ray~observables. Beyond simple average quantities, the study of distributions and correlations in prompt data, e.g., multiplicity-dependent neutron and \gray~spectra, angular distributions of the emitted particles, \(n\)-\(n\), \(n\)-\(γ\), and \(γ\)-\(γ\)~correlations, can place stringent constraints on fission models and parameters that would otherwise be free to be tuned separately to represent individual fission observables. The FREYA~and CGMF~codes have been developed to follow the sequential emissions of prompt neutrons and \(γ\)-rays~from the initial excited fission fragments produced right after scission. Both codes implement Monte Carlo techniques to sample initial fission fragment configurations in mass, charge and kinetic energy and sample probabilities of neutron and \(γ\)~emission at each stage of the decay. This approach naturally leads to using simple but powerful statistical techniques to infer distributions and correlations among many observables and model parameters. The comparison of model calculations with experimental data provides a rich arena for testing various nuclear physics models such as those related to the nuclear structure and level densities of neutron-rich nuclei, the \(γ\)-ray~strength functions of dipole and quadrupole transitions, the mechanism for dividing the excitation energy between the two nascent fragments near scission, and the mechanisms behind the production of angular momentum in the fragments, etc. Beyond the obvious interest from a fundamental physics point of view, such studies are also important for addressing data needs in various nuclear applications. (See text for full abstract.)